A Clinical Evaluation of ‘Sharngyadi Churna’ and Herbal Nebulizer in the Management of Tamaka Shwasa w.s.r. to Bronchial Asthma : A Research Article. - Prakash, Prem; Sharma, Mayukh; Sharma, Brahmanand (International Research Journal of Ayurveda & Yoga, 2023)
Tamak shwasa is a type of Shwasa Roga in which patients feel excessive difficulty in breathing and drowning in the dark. It may be defined as a disease in which vitiated “Pranvayu” combines with deranged “kapha dosha” in the lungs, causing obstruction in the “Pranavaha srotasa” (respiratory passage). A number of indigenous drugs have been claimed in various text books of Ayurveda, to be effective in the treatment of Tamak shwasa (Bronchial asthma). The shrangyadi churna is one of them. Nebulizer, a drug delivery system is based on aerosol principal and plays a very important role in asthma treatment; especially it is better for children, elderly patients, disabled individuals or those with diseases that make using their hands and taking deep breaths impossible. It delivers medication directly to the lungs. In aerosol through a nebulizer medicines passes straight into lungs and takes less time to work than orally medications. So a study was planned to evaluate the role of shrangyadi churna as a safe formulation for Tamak shwasa (Bronchial asthma) and a formulation of herbal drugs (Pushkar mulaadi yog ), in the form of alcohol based extract was planned for study as nebulizer medicine for the same purpose in this disease.